THE INFLUENCE OF PROFITABILITY AND LEVERAGE ON COMPANY VALUE WITH GOOD CORPORATE GOVERNANCE AS MODERATING VARIABLES - Dodi Suryadi (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2022)
The motivation behind this review was to look at the impact of benefit and influence on firm worth with GCG as a directing variable of exact investigations on assembling organizations recorded on the Indonesia Stock Trade 2014-2018. Information investigation in this review utilized relapse to decide the impact of the factors engaged with the review. The aftereffects of the examination are, to some degree the benefit variable altogether affects firm worth with prob. 0.0000 and influence essentially affects firm worth with prob level. 0.0062. All the while, productivity and use factors fundamentally affect firm worth with prob level. 0. 00000. The worth of R2 acquired is 0. 964539 which implies the commitment of the free factor is 96, 45% to the reliant variable. To some degree, the productivity variable has no impact on the worth of the organization which is directed by GCG with a prob esteem. of 0.5547. Somewhat, the influence variable has no impact on the worth of the organization which is directed by GCG with a prob esteem. of 0.4766. All the while, benefit and use factors have a positive and critical impact on firm worth directed by GCG with a prob level. 0.00000. The worth of R2 got is 0.966961, which implies that the commitment of the autonomous variable is 96.69% to the reliant variable.